Дослiдження електромiграцiї та дифузiї в скануючiй зондовiй мiкроскопiї твердих електролiтiв - Morozovska, A. N.; Obukhovskyi, V. V.; Udod, O. V.; Kalinin, S. V.; Tselev, O. (Publishing house "Academperiodika", 2019)
The local mechanico-electrochemical response of solid electrolytes has been simulated numerically and analyzed in the Boltzmann–Planck–Nernst–Einstein approximation with regard for the Vegard mechanism. The geometry of the problem is selected to be typical of electrochemical strain microscopy (ESM) experiments. The frequency spectra for various components of the electrolyte surface displacement and the ESM response depth are calculated, as well as the variations of donor concentrations. The corresponding comparative analysis is carried out.